Son of God : divine sonship in Jewish and Christian antiquity - Allen, Garrick V.; Akagi, Kai; Sloan, Paul (Religious educator); Nevader, Madhavi, 1976- (Eisenbrauns, 2019)
"An interdisciplinary exploration of the diverse discourse on divine sonship in ancient Jewish and Christian literature. Authors focus on a range of issues including messianism, deification, eschatological figures, Jesus, interreligious polemics, and the Roman and Jewish backgrounds of early Christian writers and the authors of the Dead Sea Scrolls"--Provided by publisher